Comparative economic, environmental and productivity assessment of a concrete bathroom unit fabricated through 3D printing and a precast approach - Weng, Yiwei (2021)
The purpose of this study is to perform a comparative study of economic cost, environmental impacts, and productivity associated with manufacturing a prefabricated bathroom unit (PBU, L: 1620 mm; W: 1500 mm; H: 2800 mm) via extrusion-based 3D concrete printing (3DCP) and a precast approach, respectively. The scope of this study includes material consumption, electricity expenditure, labor cost/productivity, and installation cycle. The results reveal that a PBU fabricated by 3DCP achieves a reduction of 25.4% in overall cost, 85.9% in CO emission, and 87.1% in energy consumption compared to the precast one. 3DCP also realizes a PBU with reduced self-weight (i.e., 26.2% lighter) and higher productivity (i.e., 48.1% improved) compared to the precast one. The above enhancements were found to be ascribed to the formwork-free fabrication in 3DCP. Finally, sensitivity analysis reveals the significance of formwork re-usage to the outcomes and demonstrates the potentials of 3DCP for small batches or customized manufacturing of PBUs. 2